Evaluation of clinical and serological responses after full-mouth implantation in single-visit versus multiple-session surgery - Atabak Kashefimehr; Amirreza Babaloo; Ahmad Afrashteh (Journal of Advanced Periodontology and Implant Dentistry)
Background. This research aimed to evaluate the clinical characteristics of pain and wound healing and serological inflammatory markers after full-mouth implantation in one session compared to several sessions. Methods. A single-masked clinical trial was conducted on 20 patients (n=10) receiving full-mouth implants. Patients were randomly divided into two groups. The first group was operated under general anesthesia in one session and the second group in multi-sessions. Inflammation level was evaluated through white blood cell (WBC) and serum C-reactive protein (CRP) before and after surgery by a blood test. Pain and early wound healing (EHS) assessment was conducted after surgery with VAS and EHS indicators, respectively. Serological and clinical parameters were compared by repeated-measures ANOVA and Sidak and Man-Whitney U tests, respectively, using SPSS 20. Results. The CRP level 48 hours postoperatively was not different in the two groups; however, seven days after treatment, it was higher in the multi-session group than in the single-session approach. The WBC was not different between the two groups at evaluated intervals. Serum levels of WBC and CRP increased 48 hours postoperatively and decreased seven days later. EHS showed no difference between the two groups at the three investigated intervals. The amount of VAS 24 and 48 hours and 7 days postoperatively was higher in multi-session surgery than in the one-session approach. In both groups, VAS was not different at 24 and 48 hours postoperatively and decreased over seven days. Conclusion. Full-mouth implant surgery under general anesthesia in one session caused less inflammation and pain postoperatively while presenting the same wound-healing process as the multi-session surgery